Pemanfaatan Articial Intelligence (AI) dalam Pembelajaran SMP - Maulidya, Sity Rahmy; Sri Ulfa Insani; Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This Community Service Research was conducted at SMP Negeri 2 Mandau. The problem faced by partners is the limited knowledge about AI and its use in learning. Thus, the purpose of this training is so that teachers have sufficient knowledge and understanding of AI so that they can use it in learning practices at school. With various features offered by the Kahoot application, learning becomes interactive, this is also supported by a lot of literature and research stating that learning with Kahoot can attract students' interest in learning. The results of this training are that teachers gain additional and in-depth knowledge about AI applications, an introduction to the Kahoot application and the practice of making quizzes or formative evaluation questions for each teacher according to the subjects taught at school. All the activities that were trained went smoothly, the teachers were actively involved and enthusiastic in the practice of making evaluation questions with Kahoot.